PENGARUH KOMUNIKASI KERJA, BEBAN KERJA DAN KONFLIK KERJA TERHADAP KINERJA KARYAWAN PT. HADJI KALLA CABANG KENDARI - Rizki, Selvi Dilyanti; Patulak, Lucia Evianti; Makmur, Muh. Rizaldi; Badia, Bahdin Ahad (Jurnal Manajemen, 2023)
This study aims to analyze the effect of work communication, workload and work conflict on the performance of employees of PT. Hadji Kalla Kendari branch. The population in this study are employees of PT. Hadji Kalla Kendari branch. The sampling method used purposive sampling where the determination of the number of samples using the slovin formula, the number of samples in this study were 56 respondents. Methods of data collection by distributing questionnaires to respondents. The data analysis technique for the data in this study used multiple linear regression analysis. The results of this study indicate that work communication, workload and work conflict simultaneously have a positive and significant effect on employee performance, work communication has a positive and significant effect on employee performance, workload has a positive and insignificant effect on employee performance and work conflict has an influence negative and not significant to employee performanceThis study aims to analyze the effect of work communication, workload and work conflict on the performance of employees of PT. Hadji Kalla Kendari branch. The population in this study are employees of PT. Hadji Kalla Kendari branch. The sampling method used purposive sampling where the determination of the number of samples using the slovin formula, the number of samples in this study were 56 respondents. Methods of data collection by distributing questionnaires to respondents. The data analysis technique for the data in this study used multiple linear regression analysis. The results of this study indicate that work communication, workload and work conflict simultaneously have a positive and significant effect on employee performance, work communication has a positive and significant effect on employee performance, workload has a positive and insignificant effect on employee performance and work conflict has an influence negative and not significant to employee performance